Teori Kendali Klasik Versus Prinsip Maksimum Pontryagin dalam Pembentukan Strategi Kendali Poros Tukik Satelit Siaran Langsung - Adi Sadewo Salatun (Institute for Research and Community Services (LPPM) ITB, 1986)
Abstract. This paper describes the development of pitch control strategy for space craft possessing a Direct Broadcasting Satellite configuration which is assumed to consist of a main rigid body plus large flexible solar arrays. The bias momentum concept of the double gimballed reaction wheel is applied for generating the pitch control torques. It is found that the wheel acceleration/deceleration produces an undesired cross coupling in roll, yaw, and pitch axis, In order to minimize this coupling, the pitch control strategy is then constructed based on the Pontryagin's Maximum principle. For comparison the classical second order theory is also applied. It can be shown that the application of maximum principle results in a better control strategy. Sari. Tulisan ini menyajikan perancangan strategi kendali poros tukik suatu wahana antariksa yang memiliki konfigurasi Satelit Siaran Langsung yang terdiri dari badan utama kaku dan panel surya lentur berukuran besar. Konsep pengubahan momentum roda reaksi dua engsel diterapkan untuk membangkitkan torsi kendali poros tukik. Dalam analisis di sini ditemukan kopling silang (cross coupling) pada ketiga poros olah gerak wahana. Untuk memperkecil kopling tersebut, strategi kendali poros tukik dibangun berdasarkan prinsip maksimum dari Pontryagin. Sebagai pembanding, teori kendali klasik orde dua juga diterapkan. Di sini dapat ditunjukkan kelebihan prinsip maksimum Pontryagin.